Editorial Board and Guideline for the Authors - EDUCARE, Editor Journal (EDUCARE, 2015)
This journal, with ISSN 1979-7877, was firstly published on August 17, 2008, in the context to commemorate the anniversary of Indonesian Independence Day. Since issue of February 2009 to date, the EDUCARE journal has been organized by the Lecturers of FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto) in Central Java; and published by Minda Masagi Press, as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The EDUCARE journal is published twice a year, i.e. every August and February.Dr. Haji Syamsuhadi IrsyadHonorable Patron of theÂ EDUCAREÂ Journal in Bandung; and Rector of UMP (Muhammadiyah University of Purwokerto) in Central Java, Indonesia.Â